2022
DOI: 10.3389/fcvm.2022.950389
|View full text |Cite
|
Sign up to set email alerts
|

Utility of PREDICT-HF score in high-risk Asian heart failure patients receiving sacubitril/valsartan

Abstract: ObjectiveThe aim of this study was to investigate the application of sacubitril/valsartan in clinical practice and the utility of PREDICT-HF score for outcome prediction in Asian heart failure patients with difference risk profiles.MethodsThe TAROT-HF study was a multicenter, single-arm, observational study. Totally 1,187 outpatients with HFrEF treated with sacubitril/valsartan were enrolled and categorized by: (1) high-risk group with ≥1 of the following three risk factors: old age (≥80 years), low baseline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Various studies reported the discontinuation of Sacubitril/Valsartan therapy due to side effects, such as hypotension and hyperkalemia. 24 However, none of the patients discontinued therapy because of hypotension in the current study as only a few patients (<5%) reported hypotension in the current study.…”
Section: Discussionmentioning
confidence: 54%
“…Various studies reported the discontinuation of Sacubitril/Valsartan therapy due to side effects, such as hypotension and hyperkalemia. 24 However, none of the patients discontinued therapy because of hypotension in the current study as only a few patients (<5%) reported hypotension in the current study.…”
Section: Discussionmentioning
confidence: 54%
“…A multivariable Cox proportional hazards model was computed to assess the factors associated with reaching the vericiguat maximal daily dose at any given time over the 90 days of follow-up. The model included the time to reach the maximal daily dose during the 90 days of follow-up as the outcome and was adjusted for known predictors of HF medication uptitration [ 26 , 27 ], such as age, sex, comorbidities, and the use of HF medications and non-pharmacological therapies. The model computed hazard ratios (HRs) with 95% confidence intervals (CIs) for each variable included.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Taiwan Society of Cardiology-Heart Failure Registry with Reduced Ejection Fraction Registry, 10 which is a prospective multicenter observational survey of patients with HFrEF recently admitted for HF in 21 hospitals from 2013 to 2014. (2) The Treatment with angiotensin receptor neprilysin inhibitor for Taiwan Heart Failure patient study, 11,12 which was a principal investigator-initiated multicenter retrospective HFrEF study that recruited symptomatic patients with HFrEF from 10 hospitals from 2017 to 2018.…”
Section: Study Design and Patient Characteristicsmentioning
confidence: 99%